The Effectiveness of the Mind Mapping Model on Elementary School Students’ Learning Outcomes in Indonesian Language Subjects - Faridah Zahrotul Ainia; Pance Mariati; Rudi Umar Susanto; Sunanto Sunanto (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the effectiveness of the Mind Mapping learning model on the learning outcomes of fourth-grade students at SDN 207 Gresik in the Indonesian language subject. The background of this research is the low student achievement in understanding reading materials, identifying main ideas, and connecting information within texts—primarily caused by the use of conventional, less engaging teaching methods. The Mind Mapping model was chosen because it is believed to help students visually and logically organize information, thereby enhancing conceptual understanding and critical thinking skills. This research employed an experimental method with a pretest-posttest control group design. The sample consisted of 30 randomly selected fourth-grade students. The instruments used included multiple-choice and essay tests as well as student perception questionnaires. The validity and reliability tests indicated that all instruments met the necessary standards. The t-test results showed a significant improvement in student learning outcomes after implementing the Mind Mapping model in the experimental class compared to the control class. In conclusion, the application of the Mind Mapping learning model is effective in improving student achievement in the Indonesian language subject and can serve as an innovative alternative teaching strategy in elementary education.